Lactate dehydrogenase A silencing in IDH mutant gliomas. Issue 5 (22nd December 2013) - Chesnelong, Charles; Chaumeil, Myriam M.; Blough, Michael D.; Al-Najjar, Mohammad; Stechishin, Owen D.; Chan, Jennifer A.; Pieper, Russell O.; Ronen, Sabrina M.; Weiss, Samuel; Luchman, H. Artee; Cairncross, J. Gregory
Abstract: Background: Mutations of the isocitrate dehydrogenase 1 and 2 gene ( IDH1/2 ) were initially thought to enhance cancer cell survival and proliferation by promoting the Warburg effect. However, recent experimental data have shown that production of 2-hydroxyglutarate by IDH mutant cells promotes hypoxia-inducible factor (HIF)1α degradation and, by doing so, may have unexpected metabolic effects. Methods: We used human glioma tissues and derived brain tumor stem cells (BTSCs) to study the expression of HIF1α target genes in IDH mutant ( mt ) and IDH wild-type ( wt ) tumors. Focusing thereafter on the major glycolytic enzyme, lactate dehydrogenase A ( LDHA ), we used standard molecular methods and pyrosequencing-based DNA methylation analysis to identify mechanisms by which LDHA expression was regulated in human gliomas. Results: We found that HIF1α-responsive genes, including many essential for glycolysis ( SLC2A1, PDK1, LDHA, SLC16A3 ), were underexpressed in IDH mt gliomas and/or derived BTSCs. We then demonstrated that LDHA was silenced in IDH mt derived BTSCs, including those that did not retain the mutant IDH1 allele (mIDH wt ), matched BTSC xenografts, and parental glioma tissues. Silencing of LDHA was associated with increased methylation of the LDHA promoter, as was ectopic expression of mutant IDH1 in immortalized human astrocytes. Furthermore, in a search of The Cancer Genome Atlas, we found low expression and high methylation of LDHA in IDH mt glioblastomas. Conclusion: To our knowledge, this is the first demonstration of downregulation of LDHA in cancer. Although unexpected findings, silencing of LDHA and downregulation of several other glycolysis essential genes raise the intriguing possibility that IDH mt gliomas have limited glycolytic capacity, which may contribute to their slow growth and better prognosis.